A inclusão política e a salvaguarda de direitos humanos de pessoas presas no Brasil - Dias, Anna Caroline Queiroz (2018)
The present study seeks to understand why the human rights of prisoners in Brazil are not fulfilled even in the face of extensive domestic legislation and international oversight of bodies such as the Inter-American Court of Human Rights. The hypothesis raised in the study is that one of the reasons justifying the numerous attacks on specific rights of people imprisoned in Brazil is in the fact that these people, in committing their crimes and being imprisoned, have their character of belonging in the original political community denied. In order to understand these processes, a historical retrospective of the sedimentation of the prison sentence was carried out in the period of Western modernity, and it was found that this penalty served not only to attend to liberal discourses of humanity, but also to a utilitarian discipline of bodies for a new society supported by values of the bourgeoisie that required an economy of punitive power. The discourse that the prison sentence from then on removed only the right of "freedom", dialogues with the liberal political philosophy in vogue in the eighteenth century. However, not only the withdrawal of individual liberty was in check in prison, but also political freedom. The effects of this suppression of political freedom in correspondence with the decadence of the individual as a citizen sustained by contractualist theories, for which the criminal would be a traitor or enemy, generated effects of exclusion that transcend the punitive segregation of prison bars. To analyze this, an Arendtian re-interpretation was proposed to understand how the human condition of action, dialogue and plurality is obstructed in the prison context and how the internal expulsion of the political community itself corresponds to the expulsion of humanity itself, leaving the person in prison in a state of abstract nudity. Finally, considering the Arendtian concept that there is no human life when it cannot be lived among men, a brief reflection was proposed in Putnam on the mitigation of the effects of political exclusion through associativism and fomenting a virtuous circle that can instill cooperation and mutual trust between prisoners and nonprisoners and between society at large.